A Unique Case of Concomitant Intraspinal Epidermoid Cyst and Lipoma Associated with Tethered Cord Syndrome - Shrey Jain; Medha A. Vyas; Ajit K. Sinha (Indian Journal of Neurosurgery)
Patients presenting with pain in lower back and paresthesia in lower limbs may have tethered cord causing the symptomology. Tethered cord may be associated with intradural tumors causing symptoms due to progressive increase in size. Association of tethered cord with single intradural tumor is a common occurrence but, to date, only one case has been reported of tethered cord associated with intradural lipoma and epidermoid cyst. The authors would like to present a similar case in a middle-aged patient.